Tratamento de dados pessoais em grupos de pesquisa à luz da lei geral de proteção de dados: estudo de caso de um grupo de pesquisa da Universidade Federal de Sergipe (UFS) - Ferreira, Nayca Negreiros (2023)
The object of this dissertation was to investigate whether the rules of the General Data Protection Act (LGPD) are being applied in the processing of personal data within research groups. Based on this research question, a case study was carried out in the Entrepreneurship and Innovation Research Laboratory (LEI) group at the Federal University of Sergipe (UFS), through descriptive and exploratory research, based on the precepts of Yin (2015), by observing the google drive of the Entrepreneurship and Innovation Research Laboratory (LEI) at the Federal University of Sergipe (UFS). The research had the following specific objectives: to verify the existence of consent for personal data collected from researchers in the LEI group; to analyze whether the storage and/or disposal of data collected before the LGPD came into force was carried out in accordance with the law; to create a manual of good practices for processing personal data within research groups. The results of the analysis pointed to a high degree of vulnerability on the part of the LEI Group due to non-compliance with certain articles of the LGPD. As a final product, a manual of good practices for processing personal data was created that can be used by all research groups in order to clarify the main rights and duties of the actors involved in research, mitigating risks and bringing greater legal certainty to the projects developed.